Chromosomal study of Xanthomonas atrovariens 'Variegatum Monostrum' a member of Araceae (Jahangirnagar University Journal of Biological Sciences, 2021)
Abstract not availableJahangirnagar University J. Biol. Sci. 9(1 & 2): 133-137, 2020 (June & December)